(3GdeTcdGJ GdeOfjI h eTcdGJ GdCMhGd GdTNUjI ddeSjMjjf ai Xd GdfXGe GdbGfhfj GdeUQj (B/ s - (3fHjd dhbG HHGhjs; (3MSf YHOGdHGSW LejYj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3eTcdI GdGMhGd GdTNUjI ddeSjMjjf jYGfi efgG MhGdi YTQI edjhf eSjMi ai eUQ MjK Gf GdbGfhf GdeWHb Ydjge ai GdGMhGd GdTNUjI Qbe 264 dSfI 1955 h ef GdbGfhf Qbe 1 dSfI 2000 jfU Ydi 9 MGdGJ JLjR GdWdGb QZe Gf GdGfLjd dG jhLO GdG MGdI hGMOI JLjR GdWdGb h gi GdWdGb dYdI GdRfG dPdc jJVQQ GdeSjMjjf WhGFage GdGQKhPcSjI h GdcGKhdjcjI h GdHQhJSJfJjfI ef JWHjb bGfhf Ydjge jYO fUhU GdGfLjd QZe Gf GdbGYOI ai GdTQjYI GdGSdGejI GJQcge deG jOjfhf jCed GdeSjMjjf HCf jUOQ bGfhf ddGMhGd GdTNUjI jWGHb fUhU GdGfLjds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B641-652s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdGMhGd GdTNUjI ddeSjMjjfs; (3GdbGfhfj GdeUQjs; (3bGfhf OhQ GdYHGOI GdehMOs; (3JWHjb GdTQjYI GdGSdGejI Ydi GdeSjMjjfs; (3GdRhGL GdeSjMjs; (3GfYbGO GdRhGLs; (3JhKjb YbO GdRhGL GdOjfjs; (3MGdGJ GdJWdjbs; (3GdGfaUGd GdLSeGfjs; (3GdRfGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs